INNOVATION DIFFUSION OF GREEN FERTILIZER TECHNOLOGY AMONG PADDY FARMERS IN MALAYSIA - MANNAN, SOBIA (2016)
In Malaysia, paddy rice is one of the most important agricultural crops and is the main staplefoodfor the nation. Despite the continuous efforts and current initiatives, country is currently facing new challenges with respect to producing new findings, ideas, methods or technologies to increase the yield. One of the problem faced by the Malaysian government is the lack of awareness on green technologies among farmers that could help them to increase production. Therefore, diffusion of innovation is essential to enhance knowledge and awareness of green technologies among farmers. Moreover, it is also important to ensure effective communication to increase rice yield in order to meet the government's target. Therefore, this study examined the influence of innovation attributes, communication channels and awareness on Green Fertilizer Technology (GFT) adoption among paddy farmers.